2009
DOI: 10.1103/physrevlett.102.235301
|View full text |Cite
|
Sign up to set email alerts
|

Metastable Helium Molecules as Tracers in SuperfluidHe4

Abstract: Metastable helium molecules generated in a discharge near a sharp tungsten tip immersed in superfluid 4He are imaged using a laser-induced-fluorescence technique. By pulsing the tip, a small cloud of He(2*) molecules is produced. We can determine the normal-fluid velocity in a heat-induced counterflow by tracing the position of a single molecule cloud. As we run the tip in continuous field-emission mode, a normal-fluid jet from the tip is generated and molecules are entrained in the jet. A focused 910 nm pump … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 23 publications
7
77
3
Order By: Relevance
“…This study investigated a mean velocity profile in a superfluid boundary layer, motivated by numerical studies for spatially inhomogeneous thermal counterflow [74,75,78,91] and visualization experiments [35,93,94,95,96,97,98]. As a result, they found that the logarithmic velocity profile could appear in wall-bounded QT.…”
Section: Numerical Study In Quantum Turbulencementioning
confidence: 99%
“…This study investigated a mean velocity profile in a superfluid boundary layer, motivated by numerical studies for spatially inhomogeneous thermal counterflow [74,75,78,91] and visualization experiments [35,93,94,95,96,97,98]. As a result, they found that the logarithmic velocity profile could appear in wall-bounded QT.…”
Section: Numerical Study In Quantum Turbulencementioning
confidence: 99%
“…Specially targeted experiments in conjunction with theoretical analysis are needed in order to probe essential thermal superfluid physics. For this reason, the further development and application to turbulent flows of the tracking of metastable helium molecules as developed by Guo et al (2009) is highly desirable. By allowing the determination of the undisturbed normal-fluid velocity, this approach can boost thermal superfluid turbulence studies.…”
Section: Introductionmentioning
confidence: 99%
“…The numerous "islands" correspond to the normal-fluid vorticity around the superfluid rings, that is induced by the vortex-fluid couplings [13]. These normal-fluid vorticity "halos" around superfluid rings is a good method for their detection in experiments that can measure normal-fluid velocity fields [14].…”
mentioning
confidence: 99%
“…The "halos" correspond to normal-fluid flow induced by vortex couplings at the locations of superfluid vorticity. Modern experimental methods [14] that measure normal-fluid velocity fields can exploit these halos in order to detect superfluid rings in a non-invasive way. As fig.…”
mentioning
confidence: 99%